2016
DOI: 10.1007/s41063-016-0027-y
|View full text |Cite
|
Sign up to set email alerts
|

Sea-ice dynamics in an Arctic coastal polynya during the past 6500 years

Abstract: The production of high-salinity brines during 9 sea-ice freezing in circum-arctic coastal polynyas is 10 thought to be part of northern deep water formation as it 11 supplies additional dense waters to the Atlantic meridional 12 overturning circulation system. To better predict the effect 13 of possible future summer ice-free conditions in the Arctic 14 Ocean on global climate, it is important to improve our 15 understanding of how climate change has affected sea-ice 16 and brine formation, and thus finally de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…4). Previous studies reported a decrease in the concentration of benthic foraminifera in Storfjorden at that time, which was attributed to the presence of extensive ice cover (Rasmussen and Thomsen, 2015;Knies et al, 2017). The dominant components of the ST_1.5 foraminiferal assemblage were C. reniforme and M. barleeanum (Fig.…”
Section: The Period From 4 To 27 Cal Ka Bpmentioning
confidence: 76%
See 4 more Smart Citations
“…4). Previous studies reported a decrease in the concentration of benthic foraminifera in Storfjorden at that time, which was attributed to the presence of extensive ice cover (Rasmussen and Thomsen, 2015;Knies et al, 2017). The dominant components of the ST_1.5 foraminiferal assemblage were C. reniforme and M. barleeanum (Fig.…”
Section: The Period From 4 To 27 Cal Ka Bpmentioning
confidence: 76%
“…The period after 0.5 cal ka BP Modern-like conditions were established in Storfjorden at ∼ 0.5 cal ka BP (Knies et al, 2017). The ST_1.5 record displayed a decrease in SAR compared to the preceding period, a decreasing 0-63 µm fraction and low IRD delivery (Fig.…”
Section: 3mentioning
confidence: 93%
See 3 more Smart Citations